DAMPAK PUTUSAN MAHKAMAH KONSTITUSI NOMOR 226-01-17-24/PHPU.DPR-DPRD-XXII/2024 TERHADAP LEGITIMASI PEMILU - Sahbudiman Sahbudiman (Universitas Borneo Tarakan, 2025)
The Constitutional Court (MK) plays a strategic role in upholding electoral justice and safeguarding democratic legitimacy in Indonesia. Constitutional Court Decision Number 226-01-17-24/PHPU.DPR-DPRD-XXII/2024, which ordered a re-vote (Pemungutan Suara Ulang/PSU) in Electoral District I of Central Tarakan and disqualified a legislative candidate, has generated significant legal implications. This study aims to analyze the problematics of the decision within the perspective of a democratic state and its implications for the future development of electoral law. The research employs normative legal research using statutory and conceptual approaches. The findings indicate that PSU may strengthen electoral integrity and fairness; however, it also creates legal dilemmas, particularly regarding the limits of the Constitutional Court’s authority in applying the ultra petita principle. This decision highlights the importance of enhancing transparency among election organizers and strengthening regulations and supervision to prevent similar disputes and to ensure sustainable electoral legitimacy.